Understanding successful development of complex health and healthcare interventions and its drivers from the perspective of developers and wider stakeholders: an international qualitative interview study. Issue 5 (30th May 2019) - Turner, Katrina M; Rousseau, Nikki; Croot, Liz; Duncan, Edward; Yardley, Lucy; O'Cathain, Alicia; Hoddinott, Pat
Abstract : Objective: Identify how individuals involved in developing complex health and healthcare interventions (developers), and wider stakeholders in the endeavour, such as funders, define successful intervention development and what factors influence how interventions are developed. Design: In-depth interviews with developers and wider stakeholders to explore their views and experiences of developing complex health and healthcare interventions. Setting: Interviews conducted with individuals in the UK, Europe and North America. Participants: Twenty-one individuals were interviewed: 15 developers and 6 wider stakeholders. Seventeen participants were UK based. Results: Most participants defined successful intervention development as a process that resulted in effective interventions that were relevant, acceptable and could be implemented in real-world contexts. Accounts also indicated that participants aimed to develop interventions that end users wanted, and to undertake a development process that was methodologically rigorous and provided research evidence for journal publications and future grant applications. Participants' ambitions to develop interventions that had real-world impact drove them to consider the intervention's feasibility and long-term sustainability early in the development process. However, this process was also driven by other factors: the realities of resource-limited health contexts; prespecified research funder priorities; a reluctance to deviate from grant application protocols to incorporate evidence and knowledge acquired during the development process; limited funding to develop interventions and the need for future randomised controlled trials (RCTs) to prove effectiveness. Participants expressed concern that these drivers discouraged long-term thinking and the development of innovative interventions, and prioritised evaluation over development and future implementation. Conclusions: Tensions exist between developers' goal of developing interventions that improve health in the real world, current funding structures, the limited resources within healthcare contexts, and the dominance of the RCT for evaluation of these interventions. There is a need to review funding processes and expectations of gold standard evaluation.